Simultaneous analysis of butyltins and total tin in sediments as a tool for the assessment of tributyltin behaviour, long-term persistence and historical contamination in the coastal environment. (November 2020) - Furdek Turk, Martina; Ivanić, Maja; Dautović, Jelena; Bačić, Niko; Mikac, Nevenka
Abstract: This study presents a new approach for the investigation of tributyltin (TBT) behaviour and fate in the marine environment. The approach is based on a simultaneous analysis of butyltins (BuTs) and total Sn in sediments, thus enabling an assessment of long-term persistence and historical input of TBT. The study also presents first evaluation of the extent to which the TBT-antifouling paints contribute to the contamination of coastal environments with inorganic Sn; it was demonstrated that the inorganic Sn in the investigated areas primarily originates from TBT degradation. The study was conducted by analyzing BuTs and total Sn in sediments from 34 locations along the Croatian Adriatic coast. The results revealed that 85% of the locations were contaminated with both BuTs and inorganic Sn. The share of ƩBuTs/total Sn was low (<10%) even in sediments with low TBT degradation efficiency (TBT/ƩBuTs >40%), demonstrating that only small portion of TBT introduced into the water column reached the sediment before being degraded. This means that recent TBT input into the marine environment may be at least 10 times higher than the amount estimated if only BuTs levels in sediments are considered. It was also demonstrated that TBT concentration in sediments with TOC <1% is not a good indicator of the overall pollution level, even if TBT/TOC approach is used in pollution assessment. Finally, in situ investigation showed that resuspension of contaminated sediments leads to significant release of MBT and DBT into the water column, whereas TBT mainly remains in sediment. Graphical abstract: Image 1 Highlights: Simultaneous analyses of BuTs and total Sn enable assessment of overall TBT behaviour. Simultaneous analyses of BuTs and total Sn enable assessment of initial TBT input. Sn contamination of coastal environment principally originates from TBT-antifoulings. Less than 10% of the initial TBT input reaches sediment before being degraded. Contrary to MBT and DBT, TBT remains attached in the sediments during resuspension.